Development and validation of the Brazilian Portuguese version of the cardiac rehabilitation barriers scale - Ghisi G.L.M. (2012)
Background: Cardiovascular diseases show high incidence and prevalence in Brazil; however, participation in Cardiac Rehabilitation (CR) is limited and has been poorly investigated in the country. The Cardiac Rehabilitation Barriers Scale (CRBS) was developed to assess the barriers to participation and adherence to CR. Objectives: To translate, cross-culturally adapt and psychometrically validate CRBS to Brazilian Portuguese. Methods: Two independent initial translations were performed. After the reverse translation, both versions were reviewed by a committee. The new version was tested in 173 patients with coronary artery disease (48 women, mean age = 63 years). Of these, 139 (80.3%) participated in CR. Internal consistency was assessed by Cronbach's alpha, test-retest reliability by intraclass correlation coefficient (ICC) and construct validity by factor analysis. T-tests were used to assess criterion validity between participants and non-participants in CR. The applied test results were evaluated regarding patient characteristics (gender, age, health status and educational level). Results: The Brazilian Portuguese version of the CRBS had Cronbach's alpha of 0.88, ICC of 0.68 and disclosed five factors, most of which showed to be internally consistent and all were defined by the items. The mean score for patients in CR was 1.29 (SD = 0.27) and 2.36 for ambulatory patients (SD = 0.50) (p <0.001). Criterion validity was also supported by significant differences in total scores by gender, age and educational level. Conclusion: The Brazilian Portuguese version of CRBS has shown adequate validity and reliability, which supports its use in future studies.